Epidemiological and molecular assessment of a measles outbreak in a highly vaccinated population of northeast Italy. - D'Agaro, P; Molin, G Dal; Gallo, T; Rossi, T; Santon, D; Busetti, M; Comar, M; Campello, C (Epidemiol Infect, 2011)
Two distinct measles outbreaks, unrelated from the epidemiological point of view but caused by genetically related strains, occurred in the Friuli Venezia Giulia region of northeastern Italy. Forty-two cases were reported during the period April-May 2008. In the first outbreak the index case was a teacher who introduced the virus into the Pordenone area, involving eight adolescents and young adults. The other concomitant outbreak occurred in the city of Trieste with 33 cases. The containment of the epidemics can be explained by the high MMR vaccine coverage in an area where the first dose was delivered to 93·4% and the second dose to 88·3% of the target children. Phylogenetic analysis of 14 measles virus strains showed that they belonged to a unique D4 genotype indistinguishable from the MVs/Enfield.GBR/14.07 strain, probably introduced from areas (i.e. Piedmont and Germany) where this genotype was present or had recently caused a large epidemic.
Keywords: Adolescent; Adult; Chi-Square Distribution; Child; Child, Preschool; Community-Acquired Infections; Disease Outbreaks; Female; Humans; Immunization Schedule; Infant; Italy; Male; Measles; Measles Vaccine; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny